Anti-metal diffusion nano-coating composite anode, preparation method thereof and solid oxide fuel cell stack
Patent Information
- Application Number
- CN202611021118.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]本申请的主要目的是提供一种抗金属扩散纳米涂层复合阳极及其制备方法、固体氧化物燃料电池电堆,旨在解决现有技术难以有效阻隔阳极中金属元素向电解质扩散的问题
本申请中单层涂层的主体氧化物选择氧化锆、氧化铝、氧化铈以及镧锰氧化物,其主要提供优异的电子/离子混合导电性和高温稳定性,再通过高半径离子(如Y3+、Gd3+、Ce4+等)进行掺杂,以诱导晶格畸变,锁定高温稳定相,减少晶界迁移通道,且通过掺杂产生氧空位浓度,可捕获金属离子(Ni2+),形成静电束缚复合体,通过致密纳米晶结构与掺杂氧空位陷阱双路径抑制金属扩散,使得阻隔性能显著提高;
Smart Images

Figure CN122889764A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solid oxide fuel cell stack technology, and in particular to an anti-metal diffusion nano-coated composite anode and its preparation method, and a solid oxide fuel cell stack. Background Technology
[0002] Solid oxide fuel cell (SOFC) stacks are high-temperature electrochemical energy conversion devices that utilize oxide ceramic electrolytes and metal-based anodes to directly convert the chemical energy of fuels (such as hydrogen, methane, or syngas) into electrical energy at high temperatures (typically 600℃-1000℃). They offer advantages such as high efficiency, strong fuel adaptability, and low emissions, and have broad application prospects in distributed power generation, marine propulsion, and aviation auxiliary power. Their core components typically consist of a metal-ceramic composite anode, an oxygen-ion conductive electrolyte, and a perovskite cathode. However, during high-temperature operation (600℃-1000℃), the diffusion of metal elements (such as Ni) from the anode into the electrolyte becomes a key issue leading to performance degradation in SOFC stacks. Specifically, the diffused Ni reacts with the electrolyte (such as YSZ) to form an insulating phase (such as NiO or Ni-Zr oxide), significantly increasing interfacial resistance, thereby reducing stack efficiency, accelerating material aging, and ultimately shortening service life. Existing technologies attempt to mitigate this problem through the following approaches: (1) optimization of electrolyte materials, such as using cerium oxide-based electrolytes to improve ionic conductivity, but optimizing electrolyte materials may increase manufacturing costs and have limited blocking effect; (2) improvement of anode structure, such as introducing porous ceramic-based anodes to reduce metal content, but this may sacrifice electrochemical activity; (3) adjustment of operating conditions, such as lowering the operating temperature to slow down the diffusion rate, but lowering the temperature may reduce the overall efficiency of the stack, making it difficult to meet high power requirements. Based on this, this application proposes an anti-metal diffusion nano-coating composite anode and its preparation method. Summary of the Invention
[0003] The main objective of this application is to provide an anti-metal diffusion nano-coated composite anode and its preparation method, as well as a solid oxide fuel cell stack, aiming to solve the problem that existing technologies cannot effectively block the diffusion of metal elements from the anode into the electrolyte.
[0004] To achieve the above objectives, this application proposes an anti-metal diffusion nano-coating composite anode, comprising an anode substrate and a nano-oxide coating covering the surface of the anode substrate; The nano-oxide coating is one of a single-layer coating, a multi-layer coating, or a gradient composite coating. The components of the single-layer coating include at least one of yttrium and cerium co-doped zirconium oxide, magnesium-doped aluminum oxide, gadolinium and samarium co-doped cerium oxide, and lanthanum manganese oxide; The multilayer coating includes a conductive layer and a barrier layer stacked sequentially from the anode side, wherein the barrier layer comprises at least one of yttrium-doped zirconium oxide and magnesium-doped aluminum oxide; The gradient composite coating consists of gadolinium-doped cerium oxide with a continuously varying content from the anode side to the electrolyte side.
[0005] Optionally, the single-layer coating comprises at least one of the following components: ZrO2 doped with Y2O3 and CeO2, wherein the doping amount of Y2O3 is 7 mol%-9 mol% and the doping amount of CeO2 is 0 mol%-2 mol%. Al₂O₃ doped with MgO, wherein the doping amount of MgO is 1wt%-2wt%; CeO2 doped with Gd2O3 and Sm2O3, wherein the doping amount of Gd2O3 is 9 mol%-11 mol% and the doping amount of Sm2O3 is 0 mol%-5 mol%. LaMnO3 doped with La2O3, wherein the doping amount of La2O3 is 1wt%-2wt%.
[0006] Optionally, the conductive layer comprises CeO2 doped with Gd2O3, and the thickness of the conductive layer is 10nm-20nm; The barrier layer comprises at least one of ZrO2 doped with Y2O3 and Al2O3 doped with MgO; the thickness of the barrier layer is 30nm-60nm.
[0007] Optionally, both the outer surface of the multilayer coating and the outer surface of the gradient composite coating are coated with a functional layer. The functional layer comprises at least one of SrTiO3 and LaMnO3 doped with La2O3, and the thickness of the functional layer is 5nm-20nm.
[0008] Optionally, the gadolinium-doped cerium oxide content in the gradient composite coating decreases linearly from the anode side to the electrolyte side, wherein the gadolinium-doped cerium oxide content on the anode side is 40wt%-60wt% and the content on the electrolyte side is 0wt%.
[0009] Optionally, the outer surface of the nano-oxide coating is coated with a protective layer, the protective layer comprising at least one of Si3N4 and graphene, and the thickness of the protective layer being 3nm-8nm.
[0010] This application also proposes a method for preparing an anti-metal diffusion nano-coated composite anode, comprising the following steps: The anode substrate is pretreated to obtain a pretreated anode substrate; The nano-oxide coating is laminated onto the surface of the pretreated anode substrate using one or more of the following processes: plasma spraying, magnetron sputtering, atomic layer deposition, electrophoretic deposition, or chemical vapor deposition, to obtain a composite anode. After graded annealing, the composite anode is obtained with an anti-metal diffusion nano-coating composite anode.
[0011] Optionally, the step of pretreating the anode substrate to obtain a pretreated anode substrate includes: The anode substrate was ultrasonically cleaned using a mixture of ethanol and water at a power of 30kHz-50kHz for 15-20 minutes. The ultrasonically treated anode substrate is then subjected to plasma etching in a mixed gas of Ar and O2, with an etching power of 160W-200W and an etching time of 10min-12min. The etched anode substrate was then sandblasted with Al2O3 particles with a particle size of 50μm-100μm at a sandblasting pressure of 0.3MPa-0.4MPa to obtain a pretreated anode substrate with a surface roughness of Ra1.2μm-1.6μm.
[0012] Optionally, the step of performing graded annealing on the composite anode includes: The composite anode was annealed in an N2 atmosphere at a temperature of 500℃-600℃ for 2-3 hours, and then annealed in an Ar atmosphere at a temperature of 850℃-900℃ for 3-4 hours.
[0013] This application also proposes a solid oxide fuel cell stack, including a cathode, an electrolyte, and the aforementioned anti-metal diffusion nanocoating composite anode.
[0014] This application includes at least the following beneficial effects: In this application, the main oxides of the single-layer coating are zirconium oxide, aluminum oxide, cerium oxide, and lanthanum manganese oxide, which primarily provide excellent electronic / ionic mixed conductivity and high-temperature stability. Furthermore, high-radius ions (such as Y...) are used to... 3+ Gd 3+ Ce 4+ Doping with metal ions (such as Ni) induces lattice distortion, locks in a high-temperature stable phase, reduces grain boundary migration channels, and generates oxygen vacancy concentration through doping, which can capture metal ions (Ni). 2+ This forms an electrostatically bound complex, which inhibits metal diffusion through a dual pathway of dense nanocrystalline structure and doped oxygen vacancy traps, thus significantly improving the barrier performance. The multilayer coating in this application includes a conductive layer and a barrier layer. The conductive layer reduces the interfacial contact resistance and provides a mixed ion / electron conduction channel. The barrier layer includes yttrium-doped zirconium oxide and magnesium-doped aluminum oxide, which can inhibit the diffusion of metal ions and construct a dense nanocrystalline diffusion barrier, thereby achieving synergistic optimization of the barrier performance, thermal stability and electrochemical activity of the nano-coated composite anode. In this application, the gradient composite coating continuously and gradually changes the content of gadolinium-doped cerium oxide from the anode side to the electrolyte side, forming a solid solution with continuously changing composition at the nanoscale. This allows for a smooth transition in the coefficient of thermal expansion and ionic conductivity, reduces interfacial stress, decreases interfacial reaction products, and forms a diffusion barrier that increases from the anode side to the electrolyte side, thereby constructing a diffusion barrier with high barrier performance. This application addresses the porous characteristics of SOFC anodes by employing various processes such as suspension plasma spraying, low-pressure plasma spraying, magnetron sputtering, and a combination of atomic layer deposition / electrophoretic deposition. These processes achieve uniform coverage and strong adhesion of nano-oxide coatings on complex porous surfaces, demonstrating strong process adaptability and high coverage, thus ensuring the quality of the nano-oxide coatings. This application systematically applies nano-coating technology to SOFC anodes. By selecting nano-oxide materials such as zirconium oxide, alumina, cerium oxide, and lanthanum manganese oxide, and combining doping and composite coating design, a diffusion barrier with high barrier performance is constructed, reducing interfacial reaction products and thus lowering interfacial resistance and performance degradation rate. This significantly improves the stability and lifespan of SOFC stacks during high-temperature operation, filling the technological gap in the field of nano-coating for blocking metal diffusion in SOFC anodes. Furthermore, the three nano-oxide coating systems constructed in this application are applicable to various SOFC systems (including Ni-YSZ anodes, Ni-GDC anodes, and different electrolyte materials) and can be extended to other high-temperature fuel cells or electrolysis devices (such as solid oxide electrolyzers, SOEC). The high-temperature stability and fuel adaptability of nano-oxide coatings make them promising for applications in distributed power generation, combined heat and power, marine power, and aviation auxiliary power units. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0016] Figure 1 XPS images of the Y,Ce-ZrO2 monolayer coated anode described in this application embodiment in its initial state and after 1000 h of operation at 800°C; Figure 2 This is a diffusion depth distribution diagram of Ni element in the electrolyte as described in the embodiments of this application; Figure 3 This is a schematic diagram of the performance degradation curve of the SOFC stack described in the embodiments of this application; Figure 4 This is a schematic diagram of the life test curve of the SOFC stack described in the embodiments of this application.
[0017] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0018] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0019] To address the technical problems existing in the prior art, embodiments of this application provide an anti-metal diffusion nano-coating composite anode, comprising an anode substrate and a nano-oxide coating covering the surface of the anode substrate; The nano-oxide coating is one of a single-layer coating, a multi-layer coating, or a gradient composite coating. The components of the single-layer coating include at least one of yttrium and cerium co-doped zirconium oxide, magnesium-doped aluminum oxide, gadolinium and samarium co-doped cerium oxide, and lanthanum manganese oxide; The multilayer coating includes a conductive layer and a barrier layer stacked sequentially from the anode side, wherein the barrier layer comprises at least one of yttrium-doped zirconium oxide and magnesium-doped aluminum oxide; The gradient composite coating consists of gadolinium-doped cerium oxide with a continuously varying content from the anode side to the electrolyte side.
[0020] In this application, the main oxides of the single-layer coating are zirconium oxide, aluminum oxide, cerium oxide, and lanthanum manganese oxide, which primarily provide excellent electronic / ionic mixed conductivity and high-temperature stability. Furthermore, high-radius ions (such as Y...) are used to... 3+ Gd 3+ Ce 4+ Doping with metal ions (such as Ni) induces lattice distortion, locks in a high-temperature stable phase, reduces grain boundary migration channels, and generates oxygen vacancy concentration through doping, which can capture metal ions (Ni). 2+The process involves several key technologies: First, a multilayer coating is constructed, forming an electrostatically bound complex. This complex utilizes a dense nanocrystalline structure and oxygen vacancy traps to suppress metal diffusion, significantly improving barrier performance. Second, a multilayer coating includes a conductive layer and a barrier layer. The conductive layer reduces interfacial contact resistance and provides a mixed ion / electron conduction channel. The barrier layer, consisting of yttrium-doped zirconium oxide and magnesium-doped alumina, suppresses metal ion diffusion and constructs a dense nanocrystalline diffusion barrier. This achieves synergistic optimization of the barrier performance, thermal stability, and electrochemical activity of the nano-coated composite anode. Third, a gradient composite coating is constructed by continuously varying the gadolinium-doped cerium oxide content from the anode side to the electrolyte side, forming a solid solution with continuously changing composition at the nanoscale. This results in a smooth transition between the coefficient of thermal expansion and ionic conductivity, reducing interfacial stress, minimizing interfacial reaction products, and creating an increasing diffusion barrier from the anode side to the electrolyte side, thus constructing a diffusion barrier with high barrier performance.
[0021] Specifically, the nanoparticle size of each component of the nano-oxide coating is controlled between 5nm and 40nm. It is prepared by ball milling or sol-gel method to ensure high purity (>99.9%) and uniform particle size distribution, thereby forming a high-density nanocrystalline structure with a grain gap of <1nm.
[0022] As one possible embodiment of this application, the single-layer coating comprises at least one of the following components: ZrO2 doped with Y2O3 and CeO2, wherein the doping amount of Y2O3 is 7 mol%-9 mol% and the doping amount of CeO2 is 0 mol%-2 mol%. Al₂O₃ doped with MgO, wherein the doping amount of MgO is 1wt%-2wt%; CeO2 doped with Gd2O3 and Sm2O3, wherein the doping amount of Gd2O3 is 9 mol%-11 mol% and the doping amount of Sm2O3 is 0 mol%-5 mol%. LaMnO3 doped with La2O3, wherein the doping amount of La2O3 is 1wt%-2wt%.
[0023] Specifically, this application aims to further improve coating performance by controlling the cubic phase content in ZrO2 doped with Y2O3 and CeO2 to >95%, which optimizes crystal structure stability and oxygen vacancy concentration; the α phase content in Al2O3 doped with MgO to >90%, which improves the coating's thermal shock resistance and grain boundary strength; the fluorite structure content in CeO2 doped with Gd2O3 and Sm2O3 to >98%, which enhances ionic conductivity and thermal cycling durability; and the perovskite structure content in LaMnO3 doped with La2O3 to >95%, whose perovskite structure can provide additional catalytic activity and reduce interfacial polarization resistance. By ensuring that the monolayer coating is dominated by high-temperature stable phases (cubic phase / α phase / fluorite structure / perovskite structure), the grain boundary diffusion coefficient can be reduced to 10. -15 -10 -16 cm 2 / s, which is beneficial to improving the diffusion performance of a single-layer coating.
[0024] As one possible implementation of this application, the composition of the conductive layer includes CeO2 doped with Gd2O3, and the thickness of the conductive layer is 10nm-20nm. The barrier layer comprises at least one of ZrO2 doped with Y2O3 and Al2O3 doped with MgO; the thickness of the barrier layer is 30nm-60nm.
[0025] Specifically, CeO2 doped with Gd2O3 has a thermal expansion coefficient that matches that of the anode, which can reduce the contact resistance between the barrier layer and the anode and provide a mixed ion / electron conduction channel to enhance interfacial conductivity. ZrO2 doped with Y2O3 and Al2O3 doped with MgO can inhibit metal ion diffusion and construct a dense nanocrystalline diffusion barrier. Furthermore, the matching thermal expansion coefficients between the conductive layer and the barrier layer can prevent interlayer delamination. Through the synergistic design of the conductive layer and the barrier layer, the barrier performance, thermal stability, and electrochemical activity of the anode with this multilayer coating are significantly improved.
[0026] As one possible implementation of this application, both the outer surface of the multilayer coating and the outer surface of the gradient composite coating are coated with a functional layer. The functional layer comprises at least one of SrTiO3 and LaMnO3 doped with La2O3, and the thickness of the functional layer is 5nm-20nm.
[0027] Specifically, by introducing a functional layer on the outer surface of the multilayer coating and gradient composite coating, the functional layer adopts SrTiO3 and / or LaMnO3 doped with La2O3. SrTiO3 has excellent electronic / ionic mixed conductivity and high temperature stability, which can enhance the electrochemical compatibility of the coating with the electrolyte; while LaMnO3 doped with La2O3 can generate a trace liquid phase at high temperature, which can fill the microcracks in the coating through capillary action, further improving the durability of the coating.
[0028] As one possible implementation of this application, the content of gadolinium-doped cerium oxide in the gradient composite coating decreases linearly from the anode side to the electrolyte side, wherein the content of gadolinium-doped cerium oxide on the anode side is 40wt%-60wt% and the content on the electrolyte side is 0wt%.
[0029] Specifically, gadolinium-doped cerium oxide is CeO2 doped with Gd2O3, with a content of 40wt%-60wt% on the anode side, which can be matched with Ni-YSZ anodes, and then linearly reduced to 0wt% on the electrolyte side, thereby achieving a smooth transition of the coefficient of thermal expansion, significantly reducing thermal stress, thereby reducing interfacial reaction products, and forming a diffusion energy barrier that increases from the anode side to the electrolyte side, thus constructing a diffusion barrier with high barrier performance.
[0030] As one possible implementation of this application, the outer surface of the nano-oxide coating is coated with a protective layer, the components of which include at least one of Si3N4 and graphene, and the thickness of the protective layer is 3nm-8nm.
[0031] This application deposits an ultrathin protective layer on the outer surface of the nano-oxide coating. Si3N4 can improve the corrosion resistance and high-temperature oxidation resistance of the nano-oxide coating, while graphene can enhance the surface conductivity and mechanical toughness, thereby further improving the thermal shock resistance and corrosion resistance of the nano-oxide coating and significantly enhancing the durability of SOFC stacks under harsh operating conditions (such as frequent start-stop or fuel changes).
[0032] Embodiments of this application also provide a method for preparing an anti-metal diffusion nano-coating composite anode, comprising the following steps: S1. The anode substrate is pretreated to obtain a pretreated anode substrate.
[0033] In the specific implementation process, a mixture of ethanol and water is used to ultrasonically clean the anode substrate. The ultrasonic power is 30kHz-50kHz and the ultrasonic time is 15min-20min. The ultrasonically treated anode substrate is then subjected to plasma etching in a mixed gas of Ar and O2, with an etching power of 160W-200W and an etching time of 10min-12min. The etched anode substrate is then sandblasted with Al2O3 particles with a particle size of 50μm-100μm at a sandblasting pressure of 0.3MPa-0.4MPa to obtain a pretreated anode substrate with a surface roughness of Ra1.2μm-1.6μm. By controlling the surface roughness of the anode substrate, the adhesion of the nano-oxide coating on the anode substrate can be enhanced.
[0034] S2. The nano-oxide coating is laminated onto the surface of the pretreated anode substrate using one or more processes such as plasma spraying, magnetron sputtering, atomic layer deposition, electrophoretic deposition, or chemical vapor deposition to obtain a composite anode.
[0035] In specific implementation, the plasma spraying process is either suspension plasma spraying or low-pressure plasma spraying to improve the coverage and density of the coating on the porous anode surface. The suspension plasma spraying process uses a nanoparticle suspension with a solid content of 5wt%-10wt% and an ethanol / water mixture as the solvent. Uniform droplets are formed through ultrasonic atomization (frequency 20kHz). Spraying parameters include: plasma power 32kW-40kW, spraying distance 100mm-130mm, liquid feed rate 8mL / min-15mL / min, and carrier gas (Ar / H2=9:1) flow rate 60L / m³. The low-pressure plasma spraying process is carried out in a vacuum environment (pressure 30Pa-60Pa) with a flow rate of 75L / min and a cooling rate of 50℃ / s-100℃ / s. The process parameters are as follows: high-purity Ar / H2 plasma gas (H2 content 5%-10%) is used. By reducing the oxygen partial pressure, the oxide inclusions in the coating are reduced to <0.5wt%. In order to adapt to the anodic pore structure (pore diameter 1μm-10μm, porosity 30%-40%), a multi-angle spraying system (spray gun tilt angle 0°-45°, rotation speed 10rpm-20rpm) is developed to ensure that the coverage of the inner wall of the pores reaches more than 85%.
[0036] The magnetron sputtering process in this application employs dual-target co-sputtering technology to precisely control the composition and thickness of the multilayer coating. The optimized process parameters are: RF power 400W-650W, DC power 300W-450W, working pressure 0.2Pa-0.4Pa, substrate temperature 350℃-500℃, target-to-substrate distance 60mm-100mm, and a pulsed bias voltage (-80V to -120V, frequency 50kHz) is introduced to enhance coating density and adhesion. The residual stress of the coating is controlled within the range of -0.5GPa to 0.2GPa. To improve the uniformity of coating deposition on the porous anode surface, a three-dimensional rotating substrate fixture (rotation speed 5rpm-15rpm, tilt angle 0°-60°) can be used, combined with an online optical monitoring system (wavelength 532nm, resolution 0.1nm) to measure the coating thickness in real time, with an error control of <2nm.
[0037] In this application, atomic layer deposition (ALD) and electrophoretic deposition (ECD) processes can be combined to enhance the coating's coverage in deep pore regions and reduce its porosity. The ALD parameters are: pulse time 0.05s-0.2s, cleaning time 3s-6s, deposition temperature 250℃-350℃, and number of cycles 30-100. The ECD parameters are: electric field strength 50V / cm-100V / cm, and deposition time 1min-3min. S3. The composite anode is annealed in N2 atmosphere at 500℃-600℃ for 2h-3h, and then annealed in Ar atmosphere at 850℃-900℃ for 3h-4h to obtain an anti-metal diffusion nano-coating composite anode.
[0038] To address the high-temperature thermal cycling (600℃-1000℃, cycling rate 5℃ / min-15℃ / min) of SOFC stacks, this application employs a staged annealing process. The first stage involves annealing at 500℃-600℃ to eliminate deposition stress, while the second stage involves annealing at 850℃-900℃ to optimize the crystal structure. This results in a final coating hardness of 14GPa-20GPa and a fracture toughness of 2MPa·m. 1 / 2 -3MPa·m 1 / 2 The residual stress was reduced to -0.5GPa to 0.3GPa, thereby improving the adhesion and durability of the coating. The coating porosity was reduced to 5%-8%, and the surface roughness was reduced to Ra0.2μm-0.5μm, which optimized gas diffusion and electrochemical reaction activity, resulting in a reduction in anodic polarization resistance and improved performance and durability of the fuel cell stack.
[0039] Embodiments of this application also provide a solid oxide fuel cell stack, including a cathode, an electrolyte, and the aforementioned anti-metal diffusion nanocoating composite anode.
[0040] The technical solutions described above in this application will be explained in detail below with reference to specific embodiments.
[0041] Example 1: Preparation and performance testing of a single-layer coated anode Material and equipment selection: Anode substrate: Ni-YSZ cermet (Ni content 48wt%, porosity 38%, pore size 1μm-10μm, thickness 500μm); Nano-oxide coating material: 8 mol% Y₂O₃ + 2 mol% CeO₂ co-doped ZrO₂ (Y,Ce-ZrO₂ nanoparticles), synthesized by sol-gel method. The Y,Ce-ZrO₂ nanoparticles have a size of 12 nm, purity >99.95%, and BET specific surface area of 55 m² / g. 2 / g).
[0042] Preparation steps: Step 1: Anode Pretreatment The anode substrate was ultrasonically cleaned using a mixture of ethanol and water (mass ratio of ethanol:deionized water = 1:1) at a power of 40 kHz for 20 min. The ultrasonically treated anode substrate was then subjected to plasma etching in a mixed gas of Ar and O2 (volume ratio Ar:O2=4:1) at a power of 200W for 12 minutes. The etched anode substrate was then sandblasted with Al2O3 particles with a particle size of 80μm at a sandblasting pressure of 0.4MPa for 5s to obtain a pretreated anode substrate with a surface roughness of Ra1.3μm.
[0043] Step 2, Coating Deposition Y,Ce-ZrO2 nanoparticles were placed in a mixed solvent of ethanol and water (mass ratio of ethanol:water = 1:1), the pH was adjusted to 4.5, and 0.5 wt% polyvinyl alcohol dispersant was added. The mixture was then ultrasonically atomized at 25 kHz to obtain a suspension with droplet diameters of 10 μm-20 μm. The solid content of the Y,Ce-ZrO2 nanoparticles in the suspension was 10 wt%. A 60 nm thick Y,Ce-ZrO2 coating was sprayed onto a pretreated anode substrate using a suspension plasma spraying process. The spraying parameters were set as follows: Plasma power 35kW, spraying distance 110mm, liquid feed rate 12mL / min, carrier gas (Ar / H2=9:1) flow rate 65L / min, spray gun tilt angle 35°, substrate rotation speed 20rpm, cooling rate 80℃ / s; Simultaneously, a laser interferometer (resolution 0.1nm) is used to measure the thickness in real time at 532nm with an error of <2nm; an infrared thermometer (accuracy ±1℃) is used to monitor the temperature of the anode substrate (300℃-400℃).
[0044] Step 3, Post-processing The anode with the deposited coating in step 2 was annealed at 500°C for 2.5 h in N2 atmosphere, and then annealed at 850°C for 4 h in Ar atmosphere to obtain a Y,Ce-ZrO2 single-layer coated anode with a porosity of 6% and a hardness of 15 GPa.
[0045] Performance testing: (1) Interfacial chemical state analysis The prepared Y,Ce-ZrO2 monolayer coated anodes were characterized by X-ray photoelectron spectroscopy (XPS) after operation in the initial state and at 800℃ for 1000 h, respectively, and the results were as follows. Figure 1 The XPS plot shown.
[0046] from Figure 1 As can be seen from the data, after aging at 800℃, the spectral peaks Y 3d and Zr 3d (including Zr 3d) are... 5 / 2 and Zr3d 3 / 2 The peak shifts of Zr and Ce3d are very small, with the spectral peak position changes being less than 1.2%, indicating no phase transition and that Zr in the coating... 4+ Y 3+ Ce 4+ The high chemical stability indicates that the Y,Ce-ZrO2 monolayer coating of this application has excellent oxidation resistance and barrier properties, which improves the chemical stability and durability of the Y,Ce-ZrO2 monolayer coating anode under high temperature operation.
[0047] (2) Metal diffusion barrier performance test The diffusion depth distribution of Ni in the electrolyte in the Y,Ce-ZrO2 monolayer coated anode of Example 1 was tested using secondary ion mass spectrometry (SIMS, ION-TOF V) and high-resolution TEM-EDS line scanning (JEOL JEM-ARM200F). The results were compared with those of the uncoated Ni-YSZ anode. The test conditions were set as follows: at the anode / electrolyte interface, accelerating voltage 15 kV, beam spot size 1 nm, step depth 5 nm, and Ni concentration > 1 at% was defined as the effective diffusion depth. The test results are as follows: Figure 2 As shown.
[0048] Depend on Figure 2 It is evident that without the Y,Ce-ZrO2 monolayer coating, the diffusion depth of Ni in the electrolyte reached 110 μm, while after spraying the Y,Ce-ZrO2 monolayer coating, the diffusion depth of Ni in the electrolyte decreased to 10 μm, and the Ni diffusion flux was 10. - 18 mol / cm 2 As can be seen from the ·s, the Y,Ce-ZrO2 monolayer coating of this application can achieve a Ni blocking efficiency of up to 90%, which has excellent blocking effect.
[0049] (3) Electrochemical performance testing The Y,Ce-ZrO2 monolayer coated anode from Example 1 and the uncoated Ni-YSZ anode were respectively applied to SOFC stacks, and the polarization resistance and power density were tested. The performance degradation curves of the SOFC stacks were plotted.
[0050] Test method: Polarization resistance: AC impedance spectrum (EIS, Bio-Logic VSP-300, frequency 0.1Hz-100kHz, temperature 800℃). Power density: IV curve test (temperature 800℃, H2 flow rate 100sccm, air flow rate 200sccm); Attenuation rate: Constant power mode (0.5W / cm) 2 The data acquisition interval was 10 hours, and the operation lasted for 3000 hours. The performance degradation curve of the SOFC stack was obtained as follows: Figure 3 As shown.
[0051] Tests showed that the polarization resistance of the SOFC stack was 0.58 Ω·cm without the Y,Ce-ZrO2 monolayer coating. 2 The ohmic resistance is 0.19 Ω·cm 2 With a Y,Ce-ZrO2 monolayer coating, the polarization resistance of the SOFC stack is 0.34 Ω·cm. 2 The ohmic resistance is 0.12 Ω·cm 2 ,from Figure 3 As can be seen, after operating at 800℃ for 3000 hours, the power density of the SOFC stack without the Y,Ce-ZrO2 monolayer coating decreased from 0.5 W / cm². 2 Attenuation to 0.35 W / cm 2 The decay rate was 0.12% / 100h, while the SOFC stack with a Y,Ce-ZrO2 monolayer coating only decayed to 0.45W / cm. 2 The decay rate was 0.025% / 100h, indicating that spraying this Y,Ce-ZrO2 single-layer coating can effectively slow down the performance decay of the fuel cell stack and improve its electrochemical performance.
[0052] (4) Stack life and thermal cycling test fuel cell stack life: The Y,Ce-ZrO2 monolayer coated anode from Example 1 and the uncoated Ni-YSZ anode were respectively applied to SOFC stacks, and the SOFC stack lifetime was predicted by fitting the power density decay curve over time to the Arrhenius model under 800°C operation. The SOFC stack lifetime test curve is shown below. Figure 4 As shown.
[0053] Depend on Figure 4 It can be seen that the uncoated SOFC stack operates at 800℃ for 5000 hours, with the power density decreasing from 0.5 W / cm². 2 Attenuation to 0.30 W / cm 2 The expected lifetime is 6000 hours, while the fuel cell stack with a Y,Ce-ZrO2 single-layer coating has maintained a power density of 94% after 3000 hours of operation, with an expected lifetime of 13000 hours, during which it only decays to 0.42 W / cm². 2This indicates that spraying the Y,Ce-ZrO2 single-layer coating significantly improves the durability of SOFC stacks and extends their lifespan.
[0054] Thermal cycling test: The Y,Ce-ZrO2 monolayer coated anode from Example 1 was applied to an SOFC stack, and the temperature was increased from 600°C to 900°C by programmed temperature control at a rate of 10°C / min, with a cycle interval of 5min.
[0055] After 100 thermal cycles, the power density decay rate was <2%, the adhesion was 35 MPa, and the adhesion retention rate was 96%, indicating that the SOFC stack has high thermal cycling durability after spraying the Y,Ce-ZrO2 single-layer coating, and the Y,Ce-ZrO2 single-layer coating has high adhesion and is not easy to fall off during high-temperature thermal cycling.
[0056] Example 2: Preparation and performance testing of multilayer coated anodes Material and equipment selection: Anode substrate: Ni-GDC cermet (Ni content 45wt%, porosity 40%, thickness 600μm); Nano-oxide coating materials: GDC conductive layer: 10 mol% Gd2O3 doped CeO2 nanoparticles, particle size 15 nm; Al2O3 barrier layer: 1.5wt% MgO-doped α-Al2O3 nanoparticles, particle size 20nm; SrTiO3 functional layer: SrTiO3 nanoparticles, particle size 20nm, purity >99.9%.
[0057] Preparation steps: Step 1: Anode Pretreatment Similar to Example 1, a pretreated anode substrate with a surface roughness of Ra1.4 μm was obtained.
[0058] Step 2, Coating Deposition A GDC conductive layer was deposited on a pretreated anode substrate using atomic layer deposition (ALD) with CeCl4 and GdCl3 (molar ratio CeCl4:GdCl3 = 9:1) as precursors. The ALD parameters were set as follows: Pulse time 0.08s, cleaning time 5s, deposition temperature 320℃, 60 cycles, to obtain a 15nm thick GDC layer; Then, an Al2O3 barrier layer is prepared on the GDC conductive layer using magnetron sputtering, with the magnetron sputtering parameters set as follows: With an RF power of 450W, a DC power of 350W, a working pressure of 0.25Pa, a substrate temperature of 420℃, a target-to-substrate distance of 80mm, a pulse bias of -110V, and a substrate rotation speed of 12rpm, a 50nm thick Al2O3 barrier layer was obtained. Then, an electrophoretic deposition process was used to deposit a SrTiO3 functional layer on the Al2O3 barrier layer. The SrTiO3 nanoparticles were placed in a mixed solvent of ethanol and isopropanol (mass ratio of ethanol:isopropanol = 2:1, concentration of 4 g / L), the electric field strength was set to 100 V / cm, and the deposition time was 1.5 min, to obtain a 20 nm thick SrTiO3 functional layer.
[0059] Step 3, Post-processing The anode after the coating was deposited in step 2 was annealed at 550°C for 2 hours in N2 atmosphere, and then annealed at 900°C for 3.5 hours in Ar atmosphere. Then, a plasma chemical vapor deposition process was used, with a volume ratio of SiH4:NH3 = 1:2, a volume flow rate of 15 sccm, a deposition temperature of 450℃, and a deposition time of 45s, to deposit a 5nm thick Si3N4 protective layer on the surface of the SrTiO3 functional layer, thereby obtaining a multilayer coated composite anode with a total coating thickness of 90nm and a porosity of 5.5%.
[0060] Performance testing: The test method is the same as in Example 1, and the test results are as follows: XPS analysis revealed that Al in the coating 3+ Ce 4+ 、Sr 2+ Ti 4+ The chemical state is highly stable. After running at 900℃ for 2000h, the position of the spectral peak changes by less than 1.5%, indicating that the multilayer coating of this application has excellent antioxidant and barrier properties, which improves the chemical stability and durability of the multilayer coated composite anode under high temperature operation. After testing the metal diffusion barrier properties, the diffusion depth of Ni in the electrolyte reached 110 μm without a coating. After depositing the multilayer coating as in Example 2, the diffusion depth of Ni in the electrolyte decreased to 8 μm, and the Ni diffusion flux was 10. -19 mol / cm 2 The value of ·s indicates that the multilayer coating of this application has a Ni barrier efficiency of up to 92%, which has an excellent barrier effect. Electrochemical testing showed that the polarization resistance of the SOFC stack coated with the multilayer coating described in Example 2 was 0.31 Ω·cm. 2 The ohmic resistance is 0.11 Ω·cm 2The power density decay rate is 0.018% / 100h. Compared with the SOFC stack without multilayer coating (decay rate of 0.12% / 100h), the multilayer coating of this application can effectively slow down the performance decay of the stack and improve the electrochemical performance of the stack. After SOFC stack life test, the SOFC stack with multi-layer coating operated at 800℃ for 4000h with a power density retention rate of 93% and an expected life of 14500h, which is a significant improvement in life. After thermal cycling tests, the SOFC stack coated with multi-layer coating was heated from 600℃ to 900℃ at a rate of 10℃ / min. After 150 thermal cycles, the power density decay rate was <1.8%, and the adhesion was 38MPa. This indicates that the SOFC stack has high thermal cycling durability after being coated with this multi-layer coating, and the multi-layer coating has high adhesion and is not easy to fall off during high-temperature thermal cycling.
[0061] Example 3: Preparation and Performance Testing of Gradient Composite Coated Anodes Material and equipment selection: Anode substrate: Ni-YSZ cermet (Ni content 48wt%, porosity 38%, pore size 1μm-10μm, thickness 600μm); Nano-oxide coating materials: Gradient transition layer: 8 mol% Y2O3-doped ZrO2 nanoparticles (YSZ, particle size 15 nm), 10 mol% Gd2O3-doped CeO2 nanoparticles (GDC, particle size 20 nm). LaMnO3 functional layer: 1wt% La2O3-doped LaMnO3 nanoparticles with a particle size of 25nm.
[0062] Preparation steps: Step 1: Anode Pretreatment Similar to Example 1, a pretreated anode substrate with a surface roughness of Ra1.5μm was obtained.
[0063] Step 2, Coating Deposition A gradient transition layer was applied to the pretreated anode substrate using a low-pressure plasma spraying process, with the following spraying parameters set: Plasma power 38kW, pressure 40Pa, spraying distance 130mm, powder feed rate 22g / min, Ar / H2 airflow (H2 content 10%), substrate rotation speed 15rpm, using a dual powder feeding system (controlling the gradual change of YSZ / GDC ratio so that the GDC content decreases linearly from 60 wt% in the inner layer to 0 wt% in the outer layer) to obtain a 100nm thick gradient transition layer; A LaMnO3 functional layer was then deposited on the surface of the gradient transition layer using chemical vapor deposition. The Ar / H2 gas flow (H2 content 20%), volumetric flow rate was set to 20 sccm, deposition temperature was set to 550℃, and deposition time was set to 50 s, resulting in a 10 nm thick LaMnO3 functional layer.
[0064] Step 3, Post-processing The anode after the coating was deposited in step 2 was annealed at 500°C for 3 hours in N2 atmosphere, and then annealed at 900°C for 4 hours in Ar atmosphere. A chemical vapor deposition process was then used, with a volume ratio of CH4:H2=1:5, a volumetric flow rate of 12 sccm, a deposition temperature of 500℃, and a deposition time of 35s, to deposit a 3nm thick graphene protective layer on the surface of the LaMnO3 functional layer, thereby obtaining a gradient composite coating anode with a total coating thickness of 110nm.
[0065] Performance testing: The test method is the same as in Example 1, and the test results are as follows: XPS analysis revealed Zr in the coating. 4+ Ce 4+ La 3+ Mn 3+ Mn 4+ The chemical state is highly stable. After running at 900℃ for 3000h, the position of the spectral peak changes by less than 1%, indicating that the gradient composite coating of this application has excellent antioxidant and barrier properties, which improves the chemical stability and durability of the gradient composite coating anode under high temperature operation. After testing the metal diffusion barrier properties, the diffusion depth of Ni in the electrolyte reached 110 μm without the coating. After depositing the gradient composite coating as described in Example 3, the diffusion depth of Ni in the electrolyte decreased to 6 μm, and the Ni diffusion flux was 10. -19 mol / cm 2 The value of ·s indicates that the gradient composite coating of this application has a Ni barrier efficiency of up to 94%, which shows that it has excellent barrier effect. Electrochemical testing showed that the polarization resistance of the SOFC stack coated with the gradient composite coating described in Example 3 was 0.29 Ω·cm. 2 The ohmic resistance is 0.10 Ω·cm 2 The power density decay rate is 0.012% / 100h. Compared with the SOFC stack without gradient composite coating (decay rate of 0.12% / 100h), the gradient composite coating of this application can effectively slow down the performance decay of the stack and improve the electrochemical performance of the stack. After SOFC stack life test, the SOFC stack coated with gradient composite coating operated at 800℃ for 4000h with a power density retention rate of 94% and an expected life of 16000h, which is a significant improvement in life. After thermal cycling tests, the SOFC stack coated with the gradient composite coating was heated from 600℃ to 900℃ at a rate of 10℃ / min. After 150 thermal cycles, the power density decay rate was <1.5%, and the adhesion was 40MPa. This indicates that the SOFC stack has high thermal cycling durability after being coated with the gradient composite coating, and the gradient composite coating has high adhesion and is not easy to fall off during high-temperature thermal cycling.
[0066] In summary, this application utilizes the high barrier properties of the nano-oxide coating to reduce the diffusion depth of Ni in the anode from 80μm-120μm without coating to 6μm-11μm, and reduces the diffusion flux to 10. -19 mol / cm 2 ·s-10 -18 mol / cm 2 The coating achieves a barrier efficiency of 90% and maintains a stable chemical state on the surface after 5000 hours of operation at 900℃, with an oxidation state change of <2%. The interfacial reaction products (such as NiO or Ni-Zr oxides) are significantly reduced, which significantly reduces the interfacial resistance and performance degradation rate. The performance degradation rate is reduced from 0.12% / 100h to 0.02% / 100h, which significantly enhances the durability of SOFC stacks under high-temperature operation. Long-term stability tests show that the lifespan of the SOFC stack with the nano-oxide coating composite anode is extended to 13,000-16,000 hours (compared to only 5,000-6,000 hours without coating). Thermal cycling tests show that its performance degradation is <2%, stability is significantly enhanced, coating adhesion retention is >90%, and the coating does not peel off. Thermal cycling and long-term operation tests verify the reliability of the coating under dynamic operating conditions (such as load changes or fuel switching), providing technical support for the stable operation of SOFC stacks under complex operating conditions. Electrochemical performance tests showed that the polarization resistance of the fuel cell stack with this coating decreased to 0.3 Ω·cm. 2 -0.4Ω·cm 2 The polarization resistance without coating is 0.5 Ω·cm. 2 -0.6Ω·cm 2 This reduces the ohmic resistance by 25%-35%, with fuel cell stacks having this coating exhibiting an ohmic resistance reduced to 0.14 Ω·cm. 2 -0.16Ω·cm 2 The ohmic resistance without coating is 0.2 Ω·cm. 2The degradation rate was reduced by 20%-30%. Constant power tests showed that the degradation rate of the fuel cell stack with this coating was <0.01% / 100h, and the energy conversion efficiency was increased to 60%-65% (compared to 50%-55% without coating). This indicates that the optimized interface transition layer and coating porosity ensured the balance between gas diffusion and catalytic activity, enabling the fuel cell stack to exhibit excellent performance under various fuels (such as H2, CH4, and syngas). This application employs a variety of processes, including suspension plasma spraying, low-pressure plasma spraying, magnetron sputtering, and a combination of atomic layer deposition / electrophoretic deposition, to achieve uniform coverage and strong adhesion of nano-oxide coatings on complex porous surfaces. The coverage rate is >90%, and the strong adhesion can reach 30MPa-40MPa. The process is highly adaptable and has a high coverage rate. The three nano-oxide coating systems of this application are applicable to a variety of SOFC systems (including Ni-YSZ anodes, Ni-GDC anodes and different electrolyte materials), and can be extended to other high-temperature fuel cells or electrolysis devices (such as solid oxide electrolyzers, SOEC). The high-temperature stability and fuel adaptability of the coatings make them promising for applications in distributed power generation, combined heat and power, marine power and aviation auxiliary power units.
[0067] The above description is merely an optional embodiment of this application and does not limit the patent scope of this application. Any equivalent structural transformations made based on the inventive concept of this application and the contents of the specification and drawings of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.
Claims
1. A composite anode with an anti-metal diffusion nanocoating, characterized in that, It includes an anode substrate and a nano-oxide coating covering the surface of the anode substrate; The nano-oxide coating is one of a single-layer coating, a multi-layer coating, or a gradient composite coating. The components of the single-layer coating include at least one of yttrium and cerium co-doped zirconium oxide, magnesium-doped aluminum oxide, gadolinium and samarium co-doped cerium oxide, and lanthanum manganese oxide; The multilayer coating includes a conductive layer and a barrier layer stacked sequentially from the anode side, wherein the barrier layer comprises at least one of yttrium-doped zirconium oxide and magnesium-doped aluminum oxide; The gradient composite coating consists of gadolinium-doped cerium oxide with a continuously varying content from the anode side to the electrolyte side.
2. The anti-metal diffusion nano-coating composite anode according to claim 1, characterized in that, The single-layer coating comprises at least one of the following components: ZrO2 doped with Y2O3 and CeO2, wherein the doping amount of Y2O3 is 7 mol%-9 mol% and the doping amount of CeO2 is 0 mol%-2 mol%. Al₂O₃ doped with MgO, wherein the doping amount of MgO is 1wt%-2wt%; CeO2 doped with Gd2O3 and Sm2O3, wherein the doping amount of Gd2O3 is 9 mol%-11 mol% and the doping amount of Sm2O3 is 0 mol%-5 mol%. LaMnO3 doped with La2O3, wherein the doping amount of La2O3 is 1wt%-2wt%.
3. The anti-metal diffusion nano-coating composite anode according to claim 1, characterized in that, The conductive layer comprises CeO2 doped with Gd2O3, and the thickness of the conductive layer is 10nm-20nm. The barrier layer comprises at least one of ZrO2 doped with Y2O3 and Al2O3 doped with MgO; the thickness of the barrier layer is 30nm-60nm.
4. The anti-metal diffusion nano-coating composite anode according to claim 1, characterized in that, Both the outer surface of the multilayer coating and the outer surface of the gradient composite coating are coated with functional layers. The components of the functional layers include at least one of SrTiO3 and LaMnO3 doped with La2O3, and the thickness of the functional layers is 5nm-20nm.
5. The anti-metal diffusion nano-coating composite anode according to claim 1, characterized in that, The gadolinium-doped cerium oxide content in the gradient composite coating decreases linearly from the anode side to the electrolyte side, wherein the gadolinium-doped cerium oxide content on the anode side is 40wt%-60wt% and the content on the electrolyte side is 0wt%.
6. The anti-metal diffusion nanocoating composite anode according to claim 1, characterized in that, The outer surface of the nano-oxide coating is coated with a protective layer, the components of which include at least one of Si3N4 and graphene, and the thickness of the protective layer is 3nm-8nm.
7. A method for preparing an anti-metal diffusion nano-coating composite anode as described in any one of claims 1-6, characterized in that, Includes the following steps: The anode substrate is pretreated to obtain a pretreated anode substrate; The nano-oxide coating is laminated onto the surface of the pretreated anode substrate using one or more of the following processes: plasma spraying, magnetron sputtering, atomic layer deposition, electrophoretic deposition, or chemical vapor deposition, to obtain a composite anode. After graded annealing, the composite anode is obtained with an anti-metal diffusion nano-coating composite anode.
8. The method for preparing the anti-metal diffusion nano-coating composite anode according to claim 7, characterized in that, The step of pretreating the anode substrate to obtain a pretreated anode substrate includes: The anode substrate was ultrasonically cleaned using a mixture of ethanol and water at a power of 30kHz-50kHz for 15-20 minutes. The ultrasonically treated anode substrate is then subjected to plasma etching in a mixed gas of Ar and O2, with an etching power of 160W-200W and an etching time of 10min-12min. The etched anode substrate was then sandblasted with Al2O3 particles with a particle size of 50μm-100μm at a sandblasting pressure of 0.3MPa-0.4MPa to obtain a pretreated anode substrate with a surface roughness of Ra1.2μm-1.6μm.
9. The method for preparing the anti-metal diffusion nano-coating composite anode according to claim 7, characterized in that, The step of performing graded annealing on the composite anode includes: The composite anode was annealed in an N2 atmosphere at a temperature of 500℃-600℃ for 2-3 hours, and then annealed in an Ar atmosphere at a temperature of 850℃-900℃ for 3-4 hours.
10. A solid oxide fuel cell stack, characterized in that, It includes a cathode, an electrolyte, and a composite anode with an anti-metal diffusion nanocoating as described in any one of claims 1-6.